The Liquidity and Intellectual Capital Impact on the Stability of Islamic Microfinance Institutions: Evidence from Peak Season Period - Yayat Nurhidayat; Mochamad Edman Syarief (Politeknik Negeri Bandung, 2020)
The term of Peak Season in financial institutions may still be peculiar in the eyes of the world, but in Indonesia, this phenomenon is a real thing. It has succeeded in making some financial institutions susceptible and even bankrupt. Peak season is not unconventional from the high season, but it is far more compact. Peak session, as it means in this study, is the period in which people simultaneously withdraw their savings for seasonal needs such as Eid session, school season, New Year session, and another equal occasion. This study aims to (1) analyze the effect of liquidity risk and intellectual capital on the stability of Baitul Maal wa Tamwil Islamic Microfinance Institutions (BMT IMFI) in the peak season periods, and (2) analyze the co-movement relation between liquidity and credit risk in BMT IMFI in West Bandung Regency during 2013 -2017. By using monthly data and fixed effect estimation techniques in the Generalized Moments Method (GMM) model, this study found that liquidity risk negatively affects the stability level of IMFI. Meanwhile, the intellectual capital of BMT IMFI has a positive effect on its stability level. Based on the analysis, this study also found some interesting results for BMT IMFI liquidity management policies in the Peak Season period. Furthermore, the testing on the relation between IMFI BMT’s liquidity risk and credit risk shows an insignificant result to find out the existence of a co-movement between these two risks.